High performance GeTe thermoelectrics enabled by lattice strain construction. (1st January 2023) - Liu, Ming; Sun, Yuxin; Zhu, Jianbo; Li, Chun; Guo, Fengkai; Liu, Zihang; Guo, Muchun; Zhu, Yuke; Dong, Xingyan; Ge, Zhenhua; Zhang, Qian; Cai, Wei; et al.
Abstract: Numerous intrinsic Ge vacancies in thermoelectric GeTe not only lead to overhigh carrier concentration but also seriously deteriorate carrier mobility, which shackles its thermoelectric performance. The efficient strategy and the related underlying mechanism in suppressing intrinsic Ge vacancy, however, are rarely researched yet. Herein, we demonstrated that lattice strain could be employed to regulate the defects concentration and then optimize electrical transport performance. Theoretically, the calculated results showed that lattice strain could efficiently raise the formation energy of Ge vacancies, weakening the carrier scattering and improving the carrier mobility. Calculated band structure revealed that Sb doping and Ge vacancy introduction could promote band convergence and thus efficiently decouple the electrical transport parameters. Experimentally, lattice strain was constructed through high-energy ball milling combined with spark plasma sintering to reduce the concentration of Ge vacancy and relaxation time of phonons, leading to high carrier mobility and low lattice thermal conductivity. Additionally, we carefully modulated the nominal content of Ge, and then a high ZT of 2.0 at 723 K in Ge0.90 Sb0.08 Te alloy was obtained. This work highlights that the lattice strain can be utilized to simultaneously optimize thermal and electrical transport properties. Graphical abstract: Image, graphical abstract